Anybody can do Value at Risk: A Nonparametric Teaching Study - Yun Hsing Cheung; Robert J Powell (Australasian Accounting, Business and Finance Journal, 2012)
Value at Risk (VaR) has become a benchmark methodology among investors and banks for measuring market risk. Commercially available modelling packages can be both expensive and inflexible, thereby restricting their use by academic researchers and teachers. Using nonparametric methodology, this paper provides a step-by-step teaching study on how to use Excel to construct a VaR spreadsheet for an individual asset as well as for a portfolio. This can benefit financial modelling teachers by providing them with a readily useable teaching study on how to model VaR, as well as benefit researchers by showing them how to construct an inexpensive and flexible VaR model.
Keywords: Financial modelling; value at risk; historical nonparametric value at risk; teaching study; Microsoft Excel